Implementasi Kebijakan Kartu Indonesia Pintar dalam Meningkatkan Akses Pendidikan bagi Mahasiswa Kurang Mampu di Universitas Negeri Gorontalo - Imelda Ponelo; Nadin Cahyani Tantu; Sri Yusmita Baga; Multia N. Bau; Mohammad Farel Saba; Alexander Badjuka (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Access to higher education for the underprivileged is still a serious challenge in Indonesia, especially in areas with relatively high poverty rates such as Gorontalo Province. The Indonesia Smart College Card Program (KIP-Lecture) is present as a government policy instrument to answer this problem. This study aims to analyze the implementation of the KIP-Lecture policy in improving access to education for underprivileged students at Gorontalo State University. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews with 10 student informants who received KIP-Lecture, documentation studies, and observations. The results of the study show that the implementation of KIP-Lecture at UNG has gone well from the four dimensions of Edward III's theory, namely communication, resources, disposition, and bureaucratic structure. This program has proven to have a significant impact on improving access to education through three strategic functions, namely as an enabler that opens up college opportunities for those who were previously underprivileged, a sustainer who maintains the continuity of studies, and a protector who protects the most vulnerable groups such as orphan students who rely on this program for all their living needs. In 2025, there will be 2,275 UNG students with the status of KIP-Lecture recipients. This research emphasizes that KIP-Lecture is not just a scholarship program, but a strategic policy instrument in realizing social justice in the field of higher education.